The Effect of Optimism on Psychological Distress in Student Victims of Body Shaming - Azisah, Nurul; Ridfah, Ahmad; Ismail, Ismalandari (Polteknik Ilmu Pemasyarakatan, 2023)
Students who are victims of body shaming can experience psychological distress, namely symptoms of depression and anxiety. So it is important to maintain psychological well-being through an optimistic mindset. The aim of this research is to find out whether there is an influence of optimism on psychological distress in students who are victims of body shaming. Sampling used an accidental sampling technique with a total of 120 respondents who were Makassar State University students who were victims of body shaming. Hypothesis testing was carried out using non-linear regression analysis methods with exponential models. The results of this research hypothesis test show that there is a negative and very significant influence between optimism and psychological distress (r=-0.628; p=0.000). The contribution of optimism to psychological distress among Makassar State University students who are victims of body shaming is 39.5%. Other findings in this research show that the three aspects of optimism, namely permanence, pervasiveness and personalization, have a negative correlation with the two aspects of psychological distress, namely depression and anxiety. The conclusion in this research is that optimism has an influence on psychological distress in students who are victims of body shaming. The higher the optimism possessed by students who experience body shaming, the lower the level of psychological distress.